2019
DOI: 10.1002/ece3.5026
|View full text |Cite
|
Sign up to set email alerts
|

Gene markers for exon capture and phylogenomics in ray‐finned fishes

Abstract: Gene capture coupled with the next‐generation sequencing has become one of the preferred methods of subsampling genomes for phylogenomic studies. Many exon markers have been developed in plants, sharks, frogs, reptiles, fishes, and others, but no universal exon markers have been tested in ray‐finned fishes. Here, we identified a suite of “single‐copy” protein‐coding sequence (CDS) markers through comparing eight fish genomes, and tested them empirically in 83 species (33 families and nine orders or higher clad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 73 publications
(134 reference statements)
0
22
0
Order By: Relevance
“…Popular markers used in fish phylogenomic studies include ultra‐conserved elements (UCEs) (Alfaro et al., 2018; Chakrabarty et al., 2017; Faircloth et al., 2012, 2013, 2020; Friedman et al., 2019; Harrington et al., 2016; Longo et al., 2017; Roxo et al., 2019), exon capture (Arcila et al., 2017; Betancur‐R et al., 2019; Ilves & López‐Fernández, 2014; Ilves et al., 2017; Jiang et al., 2019; Song et al., 2017), and anchored hybrid enrichment (AHE) approaches (Dornburg et al., 2017; Eytan et al., 2015; Irisarri et al., 2018; Lemmon et al., 2012; Stout et al., 2016). Still, most genome‐scale markers targeted for fish phylogenetics have so far been selected based on the comparison of a limited number of model genomes and some threshold of similarity to define them as “single‐copy” (Li et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Popular markers used in fish phylogenomic studies include ultra‐conserved elements (UCEs) (Alfaro et al., 2018; Chakrabarty et al., 2017; Faircloth et al., 2012, 2013, 2020; Friedman et al., 2019; Harrington et al., 2016; Longo et al., 2017; Roxo et al., 2019), exon capture (Arcila et al., 2017; Betancur‐R et al., 2019; Ilves & López‐Fernández, 2014; Ilves et al., 2017; Jiang et al., 2019; Song et al., 2017), and anchored hybrid enrichment (AHE) approaches (Dornburg et al., 2017; Eytan et al., 2015; Irisarri et al., 2018; Lemmon et al., 2012; Stout et al., 2016). Still, most genome‐scale markers targeted for fish phylogenetics have so far been selected based on the comparison of a limited number of model genomes and some threshold of similarity to define them as “single‐copy” (Li et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic inference relies 100 on the analysis of orthologs, but loci implemented so far for analyses were based on the 101 comparison of a limited number of model genomes and some threshold of similarity to define 102 them as "single-copy" (Li et al 2007). A recent study implementing an explicit tree-based 103 filtering method to test for orthology revealed that one third of the 'single-copy' exons >200 bp 104 in length identified by Jiang et al (2019) were affected by paralogy, potentially biasing tree 105 inference (Hughes et al 2018). A set of 1,105 exons free of vertebrate and teleost WGD-derived 106 paralogs identified in this study resolved the phylogeny with confidence for more than 300 107 species of ray-finned fishes.…”
mentioning
confidence: 79%
“…This improvement in laboratory techniques has resulted in a number of studies using sequence 84 capture to target exons for fish phylogenomics ( resources for fishes has allowed for the comparison of a larger number of genomes for probe 88 design , and ultimately eight ray-finned fish genomes were used to identify 89 >17,000 'single-copy' exons (Song et al 2017) using a modification of the reciprocal BLAST 90 approach of Li et al (2007). A subset (4,434) of these were optimized for capture across all ray-91 5 finned fishes (Jiang et al 2019). Other sets of exon probes have been designed to target more 92 specific groups including cichlids (Ilves & López-Fernández 2014), and otophysans (Arcila et al 93 2017).…”
mentioning
confidence: 99%
“…A suite of 4,434 target loci were developed for ray‐finned fishes by Jiang et al (). Sequences of the 4,434 loci of two clupeiform species, Denticeps clupeoides and Ilisha elongata , collected in our previous experiments were used in designing RNA baits.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA samples were sheared using a Covaris M220 sonica- A suite of 4,434 target loci were developed for ray-finned fishes by Jiang et al (2019). Sequences of the 4,434 loci of two clupeiform F I G U R E 2 Geographic range of each population (circles) and collection sites (dots) at: Lake Dongting (DT), Lake Poyang (PY), Lake Nanyi (NY), Lake Tai (TH), Luan (LA), Lake Chao (CH), Lake Hongze (HZ), Lake Gaoyou (GY), main channels, and estuary area of the Yangtze River at Chongming, Luchao, and Jingjiang (SH) ).…”
Section: Dna Library Preparation Gene Capture and Sequencingmentioning
confidence: 99%